Diversity and conservation status of dragonflies (Odonata) at three streams in Donomulyo Sub-district, Malang District, Indonesia - MUHAMAD AZMI DWI SUSANTO; FATHURRAHMAN SIDIQ; SUFRAHA ISLAMIA; MUHAMMAD IQBAL PRATAMA (Nusantara Bioscience, 2024)
Abstract. Susanto MAD, Sidiq F, Islamia S, Pratama MI. 2024. Diversity and conservation status of dragonflies (Odonata) at three streams in Donomulyo Sub-district, Malang District, Indonesia. Nusantara Bioscience 16: 139-147. The aquatic environment is currently experiencing massive threats, especially from anthropogenic activities. Polluted effluent discarded in streams damages the existing ecosystems and negatively impacts various organisms. Donomulyo, a sub-district in Malang District of East Java Province, Indonesia, has many rivers and streams that are pivotal for local people and wildlife. Water quality in these aquatic bodies can be monitored using bioindicators. Odonata (dragonflies and damselflies) are bioindicators indicating environmental change in rivers and streams. Unfortunately, there has been no data regarding Odonata in the Donomulyo streams. Hence, this research aims to determine the diversity of dragonfly species at three streams in Donomulyo and its meaning for the environmental status. The research was conducted at Sengik, Kedungceleng, and Kedungsalam streams using a Visual Encounter Survey (VES) to count individuals of each dragonfly species. This study recorded 258 individuals identified into 25 species of 4 families. Aside from Copera vittata javana (Lieftinck, 1940) which International Union for Conservation of Nature (IUCN) Red List status is Not Evaluated, all other dragonflies are Least Concern evaluated. The three streams studied in this research generally had moderate Odonata diversity (2.02 < H' < 2.41), indicating good habitat conditions.